(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Bangladesh has been experiencing large dengue outbreaks since 2019, the 2023 outbreak is the largest on record. Comparing dengue profiles and out comes between outbreaks is crucial for enhancing our understanding of dengue and improving clinical and public health responses to future outbreaks. This study com pared the profile and outcome of dengue patients admitted to the Pediatric Inten sive Care Unit (PICU) of a tertiary-level hospital in Chattogram, Bangladesh, during the 2022 and 2023 outbreaks. Materials and methods: This record-based study included 81 laboratory-confirmed dengue children admitted to the PICU of Chittagong Medical College Hospital. Using SPSS Windows version 23.0, the demographics, clinical manifestations, and outcomes of the cases were compared between two outbreaks. Results: Twenty-three and 58 patients were admitted between 2022 and 2023, respectively. Median age of children was 5 years in both years. Males were affected more, with a male-female ratio of 1.5:1 in 2022, which was reversed in 2023 with a male-to-female ratio of 0.9:1. Persistent vomiting and abdominal pain was noticed to be significantly higher among patients in 2023. The median length of PICU stay was significantly higher in 2023 than in 2022 (8 vs. 5 days, p<0.001). The PICU mortality rate was lower in 2023 than in 2022 (13.8% vs. 21.7%), though it was not statistically significant. Conclusion: Though the number of PICU-admitted cases is increasing, the mortality rate is decreasing with appropriate management. So, for district-level hospitals in Bangladesh, establishing a pediatric intensive care unit is the demand of time to manage this severe variety of dengue pediatric cases. ><0.001) The PICU mortality rate was lower in 2023 than in 2022 (13.8% vs. 21.7%), though it was not statistically significant. Conclusion: Though the number of PICU-admitted cases is increasing, the mortality rate is decreasing with appropriate management. So, for district-level hospitals in Bangladesh, establishing a pediatric intensive care unit is the demand of time to manage this severe variety of dengue pediatric cases Chatt Maa Shi Hosp Med Coll J; Vol.24 (2); July 2025; Page 62-65